2004
DOI: 10.1016/s0168-583x(03)01772-5
|View full text |Cite
|
Sign up to set email alerts
|

Collisional effects on HFS transitions of antiprotonic helium

Abstract: Collisions of metastable antiprotonic helium with medium atoms induce transitions between hyperfine structure sublevels as well as shift and broadening of the microwave M1 spectral lines. We consider these effects in the framework of a simple model with scalar and tensor interactions between (pHe + ) nL and He atoms. Smatrix is obtained by solving coupled-channels equations involving 4 HFS sublevels (F = L ± 1/2, J = F ± 1/2) of the nL level and relative angular momenta up to l = 5 at the kinetic energy E 10 K… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 8 publications
1
9
1
Order By: Relevance
“…For p 4 He + theoretical calculations of Grigory Koren-434 man [22,23] confirmed that the density dependence 435 is very small. Also for p 3 He + theory predicts a col-436 lisional shift much smaller than our error bars [13].…”
mentioning
confidence: 90%
“…For p 4 He + theoretical calculations of Grigory Koren-434 man [22,23] confirmed that the density dependence 435 is very small. Also for p 3 He + theory predicts a col-436 lisional shift much smaller than our error bars [13].…”
mentioning
confidence: 90%
“…A more recent calculation [27], based on mea-surements of the collisional broadening [25], predicts ∆ = −0.048 kHz/mbar which is less than the experimental precision. As a negative slope contradicts the predictions, the average of each measurement was taken but the error used was that of the extrapolation to zero density from the fit.…”
mentioning
confidence: 85%
“…First two pairs are close to each other, whereas the third one, corresponding to double spin-flip, is suppressed by three orders of magnitude. All transition rates, shifts and broadenings of the spectral lines fall with temperature up to T = 10 K due to a displacement of mean kinetic energy from the resonances at very low energy [7,8]. …”
Section: Elementary Collisional Characteristics Of Hfs Transitionsmentioning
confidence: 97%
“…The only factor of importance can be a non-central part of the electrostatic interaction. In the papers [7,8] we have introduced the model potential in the form…”
Section: Elementary Collisional Characteristics Of Hfs Transitionsmentioning
confidence: 99%
See 1 more Smart Citation